Novel High Current-Carrying Quasi-1D Material: Nb2PdS6 - Cho, Sooheon; Jeong, Byung Joo; Choi, Kyung Hwan; Lee, Bom; Jeon, Jiho; Lee, Sang Hoon; Kim, Bum Jun; Lee, Jae Hyun; Oh, Hyung Suk; Yu, Hak Ki; Choi, Jae Young (Small, 2022)
A quasi-one-dimensional van der Waals metallic nanowire Nb2PdS6 is synthesized, and its electrical characteristics are analyzed. The chemical vapor transport method is applied to produce centimeter-scale Nb2PdS6 crystals with needle-like structures and X-ray diffraction (XRD) confirms their high crystallinity. Scanning transmission electron microscopy reveals the crystal orientation and atomic arrangement of the specific region with atomic resolution. The electrical properties are examined by delaminating bulk Nb2PdS6 crystals into a few nanometer-scale wires onto 100 nm-SiO2/Si substrates using a mechanical exfoliation process. Ohmic behavior is confirmed at the low-field measurements regardless of their thickness variation, and 4.64 nm-thick Nb2PdS6 shows a breakdown current density (JBD) of 52 MA cm−2 when the high electrical field is delivered. Moreover, with further exfoliation down to a single atomic chain, the JBD of Nb2PdS6 is predicted to have a value of 527 MA cm−2. The breakdown of Nb2PdS6 proceeds due to the Joule heating mechanism, and the Nb2PdS6 nanowires are well fitted to the 1D thermal dissipating model.
Keywords: 1D materials; Breakdown current density; Breakdown currents; Chemical Vapour Transport; High currents; Joules heating; Nb 2PdS 6; Quasi-1d material; Quasi-one dimensional; Quasi-one-dimensional; breakdown current density; chemical vapor transport; Joule heating; Nb 2PdS 6; quasi-1D materials; synthesis